2022
DOI: 10.3390/ijms23020716
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune System Response to Burn Damage—Focus on Cytokine Alteration

Abstract: In the literature, burns are understood as traumatic events accompanied by increased morbidity and mortality among affected patients. Their characteristic feature is the formation of swelling and redness at the site of the burn, which indicates the development of inflammation. This reaction is not only important in the healing process of wounds but is also responsible for stimulating the patient’s innate immune system. As a result of the loss of the protective ability of the epidermis, microbes which include b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 114 publications
0
32
0
1
Order By: Relevance
“…In the present study, we also observed NK cells, which are generally thought of as a part of the innate immune response but share lineage with T lymphocytes ( 34 ). NK cells are one of the first lines of defense against infections due to their ability to kill without histocompatibility complex recognition but has been observed to be reduced following burn injury ( 6 , 53 , 54 ). In the present study, we observed lower median levels of CD4+ lymphocytes as well as NK cells in individuals who developed NI relative to No NI and HCs ( Figures 2A, C ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we also observed NK cells, which are generally thought of as a part of the innate immune response but share lineage with T lymphocytes ( 34 ). NK cells are one of the first lines of defense against infections due to their ability to kill without histocompatibility complex recognition but has been observed to be reduced following burn injury ( 6 , 53 , 54 ). In the present study, we observed lower median levels of CD4+ lymphocytes as well as NK cells in individuals who developed NI relative to No NI and HCs ( Figures 2A, C ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, numerous biologically active substances related to inflammatory mediators are involved in the immunopathogenesis of the development of local and systemic disorders in burn injury. Cytokines, growth factors, C-reactive protein, procalcitonin and presepsin, matrix metalloproteases, reactive oxygen species, nitric oxide, structural proteins [70] and hemostasis parameters have the most significant importance in burn injury. These immunobiochemical markers are considered prognostic biomarkers in the assessment of the severity of burn injury and wound healing and, ultimately, in the personalized therapy of burn patients.…”
Section: Discussionmentioning
confidence: 99%
“…Burn injury causes changes in the transcriptome of 80% of leukocytes, which stimulates innate genes (pro - and anti-inflammatory cytokines) and inhibits adaptive immune responses ( 27 ). Neutrophil dysfunction, release from immature granulocytes, and potentially elevated levels of granulocyte macrophage colony-stimulating factor, interleukin 10 (IL-10), and other cytokines have also been observed ( 28 ).…”
Section: Discussionmentioning
confidence: 99%